Vliv projektů financovaných z Evropské unie na kvalitu aktivit neziskového sektoru pro děti a mládež - Müllerová, Šimona (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2012)
TITLE: The impact of projects financed from the European Union on the quality of NGO activities for children and youth AUTHOR: Bc. Šimona Müllerová DEPARTMENT: Department of Education SUPERVISOR: doc. PhDr. Věra Poláčková CSc. CONSULTANT: Mgr.Karolína Pávková ABSTRACT: This thesis deals with the implementation of projects financed by the European Social Fund. Through qualitative research it explores the impact of these projects on the quality of NGO activities for children and youth. Through expert survey it presents the issue from the perspective of three experts. The case studies presenta a description of five NGOs from Prague and the regions of the ČR, who implemented projects aimed at children and youth with the assistance of the ESF. The analysis of information obtained from experts and the NGOs gives an opportunity to say a few major phenomena associated with projects. The main positive effect is the possibility to pursue a wide range of activities for children and youth. The problem occurs after completion of the project and the end EU subsidies. It will be difficult to ensure the sustainability of activities for children and young people throughout their range. KEYWORDS: Non-profit organisations European social fund Projects Children and youth
Keywords: děti a mládež; non-profit organisations; children and youth; Evropský sociální fond; European social fund; projekty; neziskové organizace; projects